Stress induced experimental colitis - T. A. Stein; L. Keegan; L.-J. Auguste; B. Bailey; L. Wise (Mediators of Inflammation)
Stress induces chemical changes in the central nervous system which alters the biochemistry and physiology of the digestive tract. The present study determines arachidonic acid oxidation and damage in the colon following stress. Ten rats were stressed by the cold-restraint method; ten were controls. Stress induced 0.5 ± 0.7 (S.D.) mucosal erosions whereas controls had none. Subepithelial hemorrhage and erosions occurred only in the proximal two-thirds of the colon. Prostaglandin E2 synthesis was increased after stress compared to the control (381 ± 130 vs. 1610 ± 372 ng/g/min). Leukotriene C4 synthesis also increased after stress (4217 ± 994 vs. 11300 ± 1662 ng/g/min). Synthesis of prostaglandin E2 increased (r = 0.9381) with leukotriene C4. The response of the colon to stress is less severe than that in the stomach and may be related to regional regulation of prostaglandin and leukotriene synthesis.